Long-term safety and efficacy of certolizumab pegol in combination with methotrexate in the treatment of rheumatoid arthritis: 5-year results from the RAPID 1 trial and open-label extension. Issue 12 (5th August 2013) - Keystone, Edward; Landewé, Robert; van Vollenhoven, Ronald; Combe, Bernard; Strand, Vibeke; Mease, Philip; Shaughnessy, Laura; VanLunen, Brenda; van der Heijde, Désirée
Abstract : Objectives: To examine the safety and efficacy of 5-year administration of certolizumab pegol (CZP)+methotrexate (MTX) in patients with active rheumatoid arthritis (RA). Methods: Eligible patients from the Rheumatoid Arthritis Prevention of Structural Damage (RAPID)1 randomised controlled trial (RCT) were treated in open-label extension (OLE) with CZP 400 mg every other week (Q2W), reduced to 200 mg Q2W after ≥6 months, +MTX. Combined safety data from RCT and OLE are presented from initiation of CZP treatment to 12 wks post last visit in patients receiving ≥1 dose of CZP (Safety population, N=958). Efficacy data are presented to start of first site closure (wk 256 of CZP treatment: 52 wks in RCT+204 wks in OLE) for all patients randomised to receive CZP (intent-to-treat (ITT) population, N=783) and CZP patients who completed the 52 wk RCT and enrolled into OLE (wk 52 CZP completers, N=508). Disease Activity Score (DAS)28 (Erythrocyte Sedimentation Rate (ESR)), American College of Rheumatology Criteria (ACR) 20/50/70, Health Assessment Questionnaire – Disability Index (HAQ-DI), and patient retention (Kaplan–Meier analysis) were assessed. Results: Overall event rate per 100 patient-years (ER) of adverse events (AEs) was 290.4, most frequently: urinary tract infections (ER=7.9), nasopharyngitis (ER=7.3) and upper respiratory tract infections (ER=7.3). ER of serious AEs was 20.3 (infections=5.9, malignancies=1.2). 21 patients (2.2%) experienced an AE resulting in death (incidence rate=0.6). At wk 256 of treatment, 55.3% of the CZP ITT population were estimated to remain on treatment (68.7% if solely withdrawals due to AE or lack of efficacy were considered). In wk 52 CZP completers and CZP ITT population, DAS28 (ESR) remission rates and improvements from baseline were sustained to wk 256. Conclusions: CZP+MTX treatment provided a favourable risk-benefit profile over 5 years in patients with active RA. No new safety signals were identified.